Analisis Quality of Service (QoS) Jaringan Internet Pada Website Flexible-Learning Universitas Kristen Satya Wacana - Tasik, Irianto Liling; Efendi, Rissal (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In the era of increasingly advanced information and network technology, the need for communication and information exchange has become very important. Modern networks transfer data in a variety of applications such as voice, video, and data, which have different requirements in terms of speed, constraints, and service availability. Quality of Service (QoS) is a technology used to ensure that the Internet provides good and stable service quality to users. Wireshark is a network analysis tool used to monitor and analyze Internet network traffic. This research aims to analyze network quality when accessing the Satya Wacana Christian University Flexible-Learning website using Wireshark. QoS parameters such as throughput, delay, jitter, and packet loss are measured to evaluate network performance. The analysis results show that while throughput, delay, and jitter are relatively stable, the high packet loss rate indicates instability in data transmission. Therefore, network infrastructure improvements are needed to improve overall service quality